Should research samples reflect the diversity of the population?. Issue 2 (13th April 2004) - Allmark, P
Abstract : Recent research governance documents say that the body of research evidence must reflect population diversity. The response to this needs to be more sophisticated than simply ensuring minorities are present in samples. For quantitative research looking primarily at treatment effects of drugs and devices four suggestions are made. First, identify where the representation of minorities in samples matters—for example, where ethnicity may cause different treatment effects. Second, where the representation of a particular group matters then subgroup analysis of the results will usually be necessary. Third, ensuring representation and subgroup analysis will have costs; deciding on whether such representation is worthwhile will involve cost benefit analysis. Fourth, the representation of minorities should not be seen as mainly a locality issue. For qualitative research it is argued that the representation of diversity is often important. Given the small samples of many qualitative projects, however, the best way to ensure representation occurs is to allow a proliferation of such research, not to stipulate such representation in samples.